Question Number 10102 by konen last updated on 23/Jan/17

a−b=((a+b)/7)=((a×b)/(24)) ⇒a−b=?

Answered by mrW1 last updated on 23/Jan/17

a−b=((a+b)/7)=((a×b)/(24))=u  a−b=u  a+b=7u  a×b=24u  (a+b)^2 −(a−b)^2 =(7u)^2 −u^2 =48u^2   4×a×b=48u^2   4×24u=48u^2   u^2 −2u=0  u(u−2)=0  ⇒u=0 or 2  i.e. a−b=0 or 2

Answered by arge last updated on 24/Jan/17

7(a−b)=a+b  24(a−b)=ab    a=7(a−b)−b    a=((24(a−b))/b)    7a−7b−b=((24(a−b))/b)    7ab−8b^2^  =24a−24b  7ab−24a=8b^2 −24b  a(7b−24)=8b^2 −24b    a=((8b^2 −24b)/((7b−24)))    ((ab)/(24)) =a−b  ab=24a−24b    ((8b^3^  −24b^2 )/(7b−24))=((192b^2 −576b)/(7b−24))−24b    ((8b^3 −24b^2 )/(7b−24))=((192b^2 −576b−168b^2 +576)/(7b−24))    8b^3 −24b^2 =24b^2   8b^3 −48b^2 =0  b^3 −6b^2 =0  b^2 (b−6)=0    b=0 y  b=6    a=ind cuando a=0  a=8 cuando a=6    a−b=2∗∗∗Rta